A systematic review of factors influencing NHS health check uptake: invitation methods, patient characteristics, and the impact of interventions - Amanda Bunten; Lucy Porter; Natalie Gold; Vanessa Bogle (BMC, 2020)
Abstract Background The NHS Health Check (NHSHC) is a risk assessment for those aged 40-74 without a pre-existing condition in England, with the aim of preventing stroke, kidney disease, heart disease, type 2 diabetes and dementia. Uptake has been lower than anticipated. Ensuring that a high percentage of eligible patients receive a NHSHC is key to optimising the clinical and cost effectiveness of the programme. The aim of this systematic review is to highlight interventions and invitation methods that increase the uptake of NHSHCs, and to identify whether the effectiveness of these interact with broader patient and contextual factors. Method A systematic review was conducted according to the PRISMA checklist. Papers were eligible if they explored the impact of at least one of (i) interventions, (ii) invitation methods or (iii) broader factors on NHSHC uptake. Ten databases were searched in January 2016 and seven were searched in March 2018. Nine-hundred-and-forty-five papers were identified, 238 were screened and 64 full texts were assessed for eligibility. Nine studies were included in the review. Results The nine studies were all from peer reviewed journals. They included two randomised controlled trials, one observational cohort and six cross-sectional studies. Different invitation methods may be more effective for different groups of patients based on their ethnicity and gender. One intervention to enhance invitation letters effectively increased uptake but another did not. In addition, individual patient characteristics (such as age, gender, ethnicity and risk level) were found to influence uptake. This review also finds that uptake varies significantly by GP practice, which could be due either to unidentified practice-level factors or deprivation. Conclusions Further research is needed to assess the effectiveness of different invitation methods for different population groups. Research should examine how existing invitation methods can be enhanced to drive uptake whilst reducing health inequalities. Trial registration This systematic review was registered with PROSPERO on 22.02.2016. Registration number CRD42016035626.